A preliminary evaluation of World Heritage tourism promotion: comparing websites from Australia, China, and Mexico. Issue 3 (2nd July 2016) - Li, Jing; Whitlow, Matthew; Bitsura-Meszaros, Karly; Leung, Yu-Fai; Barbieri, Carla
ABSTRACT: World Heritage Sites (WHS), recognized for their remarkable natural and cultural values, are prime destinations for domestic and international tourists. Despite such values, limited information is available on the efficacy of promotion strategies to reach their markets. This note reports an instrument developed to evaluate WHS websites and the results from its application on government websites of Australia, China, and Mexico. These countries were selected based on their geographic location, perceived activeness in WHS promotion, and strong international tourism receipts. The evaluation instrument captured 33 attributes representing 5 dimensions: Communication, Site Attractiveness, Marketing Effectiveness, Technical Setup, and World Heritage Specifics. Results reveal significant variability in website quality, with areas identified for improvement, especially promoting specific World Heritage information. Besides sharing a validated instrument to evaluate WHS websites, this note discusses issues that need to be addressed to strengthen the web-based promotion of the United Nations Educational, Scientific and Cultural Organization's World Heritage Program.